Sinergitas Faktor Lingkungan Pendidikan Islam untuk Mewujudkan Tujuan Pendidikan Islam - Ulum, Fachrurizal Bachrul; Hidayati, Rohmah (Fahima, 2024)
Environmental factors and educational goals are important elements in Islamic education. Educational goals become a reference for carrying out learning and the environment becomes the place where the educational process takes place. Environmental factors consisting of family, school, and society can realize the main goal of Islamic education that forms Islamic personality character. For this reason, this research discusses the synergy of the Islamic education environment to realize the goals of Islamic education. This type of research is literature research by taking sources from books, journals, and other literacy related to relevant themes. Data analysis uses literature review analysis by analyzing and synthesizing the literature on the topic of discussion that has been written previously. The results of this study describe that there is a correlation between the synergy of the Islamic education environment and the realization of the goals of Islamic education. A good educational environment that is imbued with Islamic values will form good character in students.